DOI: 10.18174/557306
|View full text |Cite
|
Sign up to set email alerts
|

On the role of ribosomal proteins in stress resistance and fitness of Listeria monocytogenes : a laboratory evolution approach

Abstract: Listeria monocytogenes shows temperature-dependent and -independent responses to salt stress, including responses that induce cross-protection against other stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Indeed, studies have shown that mutations in SigB can increase fitness under sub-optimal conditions, including 0.5 M NaCl, 42°C, and blue light ( Abram et al, 2008 ; O’Donoghue et al, 2016 ; Guerreiro et al, 2020b , 2022b ). However, our previous evolution experiments with rpsU G50C mutants resulted in the selection of evolved variants with enhanced fitness ( Koomen, 2022 ). The fact that no variants were obtained with mutations in sigB or genes of the SigB operon suggested that the major negative effect on fitness did not derive from SigB activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, studies have shown that mutations in SigB can increase fitness under sub-optimal conditions, including 0.5 M NaCl, 42°C, and blue light ( Abram et al, 2008 ; O’Donoghue et al, 2016 ; Guerreiro et al, 2020b , 2022b ). However, our previous evolution experiments with rpsU G50C mutants resulted in the selection of evolved variants with enhanced fitness ( Koomen, 2022 ). The fact that no variants were obtained with mutations in sigB or genes of the SigB operon suggested that the major negative effect on fitness did not derive from SigB activation.…”
Section: Discussionmentioning
confidence: 99%
“…In Escherichia coli and B. subtilis, RpsU (ribosomal protein S21) is involved in translation initiation (Van Duin and Wijnands, 1981;Berk et al, 2006;Sohmen et al, 2015). Combined with the results above, it is conceivable that reduced fitness of L. monocytogenes rpsU G50C mutants is linked to decreased translation efficacy and/or the availability of functional 70S ribosomes (Koomen, 2022). The L. monocytogenes Lmo0762 protein, HflXr, a homolog of a ribosomesplitting factor, HflX, was also upregulated in all three rpsU G50C mutants (Supplementary Table S2).…”
Section: Descriptionmentioning
confidence: 99%
“…Indeed, studies have shown that mutations in SigB can increase fitness under sub-optimal conditions, including 0.5 M NaCl, 42°C and blue light (Abram et al, 2008;Guerreiro et al, 2022bGuerreiro et al, , 2020bO'Donoghue et al, 2016). However, our previous evolution experiments with rpsU G50C mutants resulted in the selection of evolved variants with enhanced fitness (Koomen, 2022). The fact that no variants were obtained with mutations in sigB or genes of the SigB operon suggested that the major negative effect on fitness did not derive from SigB activation.…”
Section: Discussionmentioning
confidence: 78%
“…In Escherichia coli and B. subtilis, RpsU (ribosomal protein S21) is involved in translation initiation (Berk et al, 2006;Sohmen et al, 2015;Van Duin and Wijnands, 1981). Combined with the results above, it is conceivable that reduced fitness of L. monocytogenes rpsU G50C mutants is linked to decreased translation efficacy and/or the availability of functional 70S ribosomes (Koomen, 2022). The L. monocytogenes Lmo0762 protein, HflXr, a homolog of a ribosome-splitting factor, HflX, was also upregulated in all three rpsU G50C mutants (Supplemental Table 3.3).…”
Section: Discussionmentioning
confidence: 99%